PERUBAHAN NILAI SOSIAL TRADISI PANGNGARI PADA MASYARAKAT DAYAK BANYADU DI DESA UNTANG KABUPATEN LANDAK - Kusnanto, Kusnanto; Zakso, Amrazi; Rustiyarso, Rustiyarso (Universitas Tanjungpura, 2022)
AbstrackThis study aims to determine the changes in the social value of the Pangngari Tradition in the Banyadu Dayak community in Untang Village, Banyuke Hulu District, Landak Regency. The method used in this research is qualitative with descriptive analysis. Sources of data were conducted through observation, documentation, interviews with village government leaders, elders, and members of the Pangngari group. The result of this research is that changes in the social values of the Pangngari tradition have a profound effect on the social life of the Bentinga hamlet community, Untang village, where now these changes have led to prioritizing their individual needs or interests. Factors that cause the development of the times are increasingly rapid so that humans inevitably have to follow the times. Efforts must be made to maintain this Pangngari tradition and the social values contained in it by keeping the community solid, building a sense of togetherness and the role of the village government being involved by making programs that can involve community members. The conclusion of this study is that the Pangngari tradition is still actively carried out by residents of the Bentinga hamlet, but there are changes in social values that occur along with the development of the current era, to preserve it even though there is a separate awareness and concrete actions taken by the community, as well as the local government.Keywords: Change, Social Values, Pangngari Tradition